Design, synthesis, and biological evaluation of oxazolidone derivatives as highly potent N-acylethanolamine acid amidase (NAAA) inhibitors. Issue 21 (21st February 2017) - Ren, Jie; Li, Yuhang; Ke, Hongwei; Li, Yanting; Yang, Longhe; Yu, Helin; Huang, Rui; Lu, Canzhong; Qiu, Yan
Abstract : Preventing PEA degradation by inhibition of NAAA is a novel strategy for the treatment of inflammation and pain. We reported the discovery of oxazolidone derivative as highly potent NAAA inhibitors, including2f, 3h, 3i and3j . Abstract : N -Acylethanolamine-hydrolyzing acid amidase (NAAA) is a lysosomal enzyme that catalyzes the hydrolysis of endogenous fatty acid ethanolamides (FAEs), such as N -palmitoylethanolamide (PEA). PEA exhibits anti-inflammatory and analgesic activities by engaging peroxisome proliferator-activated receptor α (PPAR-α). Preventing PEA degradation by inhibition of NAAA has been proposed as a novel strategy for the treatment of inflammation and pain. In the present study, we reported the discovery of the oxazolidone derivative as a novel scaffold for NAAA inhibitors, and studied the structure–activity relationship (SAR) by modification of the side chain and terminal lipophilic substituents. The results showed that the link chain length of C5, straight and saturated linkages were the preferred shape patterns for NAAA inhibition. Several nanomolar NAAA inhibitors were described, including2f, 3h, 3i and3j with IC50 values of 270 nM, 150 nM, 100 nM and 190 nM, respectively. Enzymatic degradation studies suggested that2f inhibited NAAA in a selective, noncompetitive and reversible pattern. Moreover, 2f showed high anti-inflammatory and analgesic activities after systemic and oral administration.